Penatalaksanaan Gigi 36 dengan Diagnosis Nekrosis Pulpa disertai Abses Periapikal Kronis - Ratu Amelia; Deli Mona (Faculty of Dentistry Universitas Andalas, 2020)
The main goal of endodontic treatment is to remove the entire microbial flora from the root canal system and promote periapical healing. Microorganisms that settle in the root system play an important role in the development and persistence of periapical lesions. Necrotic canals provide a very favorable environment for the growth of microorganisms in the root canal system. Thus, elimination of these bacteria is essential for apical and periapical healing after endodontic treatment. This case report discusses the endodontic treatment using calcium hydroxide in a necrotic pulp with chronic periapical abscess.